Geochemical advances in Arctic Alaska oil typing – North Slope oil correlation and charge history. (May 2021) - Botterell, Palma J.; Houseknecht, David W.; Lillis, Paul G.; Barbanti, Silvana M.; Dahl, Jeremy E.; Moldowan, J. Michael
Abstract: The Arctic Alaska petroleum province is geologically and geochemically complex. Mixed hydrocarbon charge from multiple source rocks and/or levels of thermal maturity is common within an individual oil pool. Biomarker and chemometric statistical analyses were used to correlate twenty-nine oils to five oil families derived from: (1) Triassic Shublik Formation (calcareous organofacies), (2) Triassic Shublik Formation (shaly organofacies), (3) Jurassic Kingak Shale, (4) Cretaceous shale (pebble shale unit and Hue Shale), and (5) Paleogene shale (Canning Formation). Age-diagnostic and source-related oil biomarker parameters establish clear genetic relationships between the normal oil-window components and their putative source designations. However, application of diamondoid analyses reveals mixed-oil accumulations with postmature charge contributions (diamondoid-rich and biomarker-poor) in many oils. Most sampled reservoirs contain a predominant charge derived from a single oil-window source plus a minor contribution from one or more higher maturity source(s). Variations in source organofacies also are recognized in the Shublik, Kingak, and Cretaceous oil families. In some cases, oils from multiple pools within a single field display relatively homogeneous geochemical profiles, suggesting a common source and migration pathway. For example, oil from the significant Pikka discovery is inferred to originate mainly from the calcareous Shublik Formation. In other cases, variability among oils from multiple pools within a single field (e.g., Milne Point, Colville River, and Northstar) likely indicates a more complex source, migration, and charge history. Results may be useful for anticipating the composition of oil charge in stratigraphic traps with low-permeability sandstone reservoirs, where oil gravity and other chemical parameters may influence economic viability. Highlights: Biomarkers classify five genetically distinct oil families by primary source rock. Diamondoids reveal end-members, mixed-maturity oil accumulations, and several co-sourced/mixed-oil samples. Source organofacies variations are shown among Shublik, Kingak, and Cretaceous oils. Complex charging is interpreted for many pools within a single field. Giant Pikka-Horseshoe oil discovery sourced from Shublik (calcareous organofacies).